The Study on Safety of Scolopendrid Aqua-acupuncture - Lim Seung-il; Kim Sung-nam; So Ki-suk; Choi Hoi-kang; Lim Jeong-a; Lee Sang-kwan; Moon Hyung-cheol; Soh Kyung-Sun; Kim Sung-chul (Journal of Pharmacopuncture, 2004)
Objective : Recently scolopendrid aqua-acupuncture has been a good effect on pain control but it has not been known about clinical safety. The purpose of this study was to investigate acute toxicity of scolopendrid aqua-acupuncture. Method : In order to prove the clinical safety of scolopendrid aqua-acupuncture, We have observed a bacteriological examination and clinical pathology test after scolopendrid aqua-acupuncture treatment. Balb/c mice were injected intravenous with Scolopendrid aquaacupuncture treatment for and acute toxicity test. We analyzed physical reaction(side effect)and clinical pathology test before and after Scolopendrid aqua-acupuncture treatment of mice and 20 patients suffering from pain, who admitted department of Acupunture and Moxibustion, College of Oriental Medicine, Won-Kwang University Kwangju hospital. Results : In the Blood agar plate and Nutrient agar plate, a bacteriological examination did not show a bacillus. In acute toxicity test, there was no mortality thus unable to attain the value. Examining the toxic response in the acute toxicity test, there was no sign of toxication. In acute toxic test, running biochemical serum test couldn't yield any differences between the control and experiment groups. In the 20 patients treated with Scolopendrid aqua-acupuncture, hematologic test did not show remarkable change. In the 20 patients treated with Scolopendrid aqua-acupuncture, Liver function test(AST, ALT, ALP) showed a slight decrease on the contrary, and abnormal rate showed a decrease of 5.0% compared with previous study. Reanl function test(BUN, Cr) and abnormal rate showed a decrease of 5.0% compared with previous study. In the 20 patients treated with Scolopendrid aqua-acupuncture, Electrolyte were normal range before and after treatment. In the Urine analysis of 20 patients, Leukocyte, Protein, Glucose, Keton, Bilirubin, U-bilinogen were not detected before and after Scolopendrid aqua-acupuncture treatment, and the rest almost made no difference.